Race, socioeconomic status, and return migration to New Orleans after Hurricane Katrina - Fussell, Elizabeth (2010)
Hurricane Katrina struck New Orleans on the 29th of August 2005 and displaced virtually the entire population of the city. Soon after, observers predicted the city would become whiter and wealthier as a result of selective return migration, although challenges related to sampling and data collection in a post-disaster environment have hampered evaluation of these hypotheses. In this article, we investigate return to the city by displaced residents over a period of approximately 14 months following the storm, describing overall return rates and examining differences in return rates by race and socioeconomic status. We use unique data from a representative sample of pre-Katrina New Orleans residents collected in the Displaced New Orleans Residents Pilot Survey. We find that black residents returned to the city at a much slower pace than white residents even after controlling for socioeconomic status and demographic characteristics. However, the racial disparity disappears after controlling for housing damage. We conclude that blacks tended to live in areas that experienced greater flooding and hence suffered more severe housing damage which, in turn, led to their delayed return to the city. The full-scale survey of displaced residents being fielded in 2009–2010 will show whether the repopulation of the city was selective over a longer period.